LAPORAN ASUHAN KESEHATAN GIGI DAN MULUT PADA KLIEN NY.YS (41 THN) DENGAN KELUHAN KARANG GIGI (KALKULUS) (Jurnal Kesehatan Siliwangi, 2020)
Plaque can develop on the entire surface of the tooth, especially along the gum line. If dental plaque accumulates and is not removed, dental plaque can harden and turn into tartar which is risk factor for gum disease. Tartar is a hard sediment which is located on the surface of the colored teeth starting yellowis, brownish, to blakish and having a rough surface. Poor oral hygiene facilitates large amounts of plaque buildup. The purpose of this case report is to get an overview of Dental and Oral Health Care for Clients Ny. YS (41 years old) with tartar cases.This paper is in the form of case report with the concept of dental and oral health care that consists of the process of assessment, diagnose, planning, implementation, evaluasi and subsequently documented. The method of caring for dental and oral health services is carried out by revealing data and facts in the medical record, observation and interviews with clients. Furthermore scaling treatments are performed. Conclusions from the result of the evaluation of care for dental and oral health services from Ms.Ys is the 7 purpose that clients centered has all been fulfilled.